MATERIAL PROPERTIES ANALYSIS OF DAMMAR GUM AND ETHYLENE VINYL ACETATE (EVA) BLEND AS A MATRIX FOR POLYMER COMPOSITE - Fikri Raihan, Muhamad
Composite material has the advantage of low specific mechanical properties dan corrosion resistance over metallic material. However, composite material often consists of synthetic material as reinforcement as well as the matrix, which is not environmentally friendly. Green composite, which consists of natural material, can be one of the solutions. This research is focusing on natural matrix material. Dammar gum is chosen to be the potential material, but it is too brittle to be used as a matrix. Polymer blending is done between dammar gum and ethylene vinyl acetate (EVA) to reduce the brittleness of dammar gum. The blending is done using an extrusion machine. Composition of EVA in the blending is investigated on several properties of the blending with variation of 10 wt.%, 20 wt.%, 30 wt.%, and 40 wt.% of EVA. Properties of blends are tested on tensile test, bending test, wettability test, and density test. The result showed that the addition of EVA on dammar gum can decrease its brittleness with indication of increased elongation and decreased modulus of elasticity. The wettability test put out results that the blends have intermediate properties between hydrophobic and hydrophilic, with unsignificant effect on addition of EVA. The density of dammar gum is decreased by the addition of EVA. A unique phenomenon can be seen in tensile strength data of blends consisting of 40 wt.% of EVA showing synergistic effect. This effect is caused by interaction on interface between both materials. This can be potential research for the future on blending of dammar gum and EVA.